Arte expandida decolonial: tensões entre a arte-vida, o corpo, a dramaturgia e as possibilidades de performar a si mesmo - Pereira, José Arnaldo (2021)
I proposed to follow the connections and clues of the notion of expanded field, identifying: art-life, the body, dramaturgy and possibilities of expanded ways of performing oneself. Thus, problematizing and constituting a centered and expanding research path between the look, the reeducation, the body of the artist himself, research guided by practice, performativity, the Indigenous Paradigm, the Actor-network Theory, as well as decolonial problematizations. What derives the notion-practice of Decolonial Expanded Art and its applicability in the cultural project arroboBOI.